"Do I want PrEP or do I want a roof?": Social determinants of health and HIV prevention in the southern United States. Issue 11 (2nd November 2022) - Harrison, Sayward E.; Paton, Mariajosé; Muessig, Kathryn E.; Vecchio, Alyssa C.; Hanson, Lyd A.; Hightow-Weidman, Lisa B.
ABSTRACT: Scaling up use of Pre-Exposure Prophylaxis (PrEP) among young men who have sex with men and transgender women (YMSM/TGW) is a critical part of the Ending the HIV Epidemic plan. This qualitative study contextualized the social determinants of health (SDOH) that can impede HIV prevention in rural North and South Carolina with 14 key informant interviews with stakeholders and 3 focus groups with YMSM/TGW ( N  = 23). A deductive-inductive approach with multiple coders was employed to identify themes related to SDOH in rural areas, including economic challenges (e.g., housing and food insecurity), neighborhood characteristics (e.g., lack of transportation), healthcare-related issues (e.g., provider shortages) and educational barriers (e.g., lack of comprehensive and inclusive sexual education). The socio-environmental context of the rural South and prioritization of local, community-based partnerships are necessary to reduce the burden of HIV.